Intercultural Challenges Among English Language Teaching Students in Inbound and Outbound Programs of Indonesia's Ministry of Education and Culture - Ani Fiani; Afria Dian Prastanti; Andhi Dwi Nugroho; Novita Sumarlin Putri; Rini Eka Sari; Rina Setyaningsih (Linguistic, English Education and Art (LEEA) Journal, 2022)
This paper shows the cultural barriers in the higher education setting and advises that the university makes certain preparations to welcome inbound and outbound students of exchange program upon their arrival. Students have accepted resources primarily generated from the university to overcome these obstacles. Therefore, as revealed by this study, the university or college is better able to identify students' needs and provide appropriate campus resources and services when they have a deeper grasp of their academic issues. The university must be equipped not only intellectually, but also socially and culturally, to meet the demands of its students. Keywords: Cultural Issues, Inbound and Outbound students